Flame Spray Synthesis of BaZr0.8Y0.2O3–δ Electrolyte Nanopowders for Intermediate Temperature Proton Conducting Fuel Cells. Issue 4 (29th June 2015) - Bozza, F.; Arroyo, Y.; Graule, T.
Abstract Flame Spray Synthesis (FSS) technique has been used for the preparation of BaZr0.8Y0.2O3–δ (BZY20) nanoprecursors. The nanoprecursors were composed of a perovskite phase mixed with doped Zirconia and barium nitrate. Pure phase powder could be obtained after calcining the precursors at 1, 200 °C. Both nanoprecursors and pure phase powder were then sintered at 1, 600 °C to obtain dense specimen. AC impedance spectroscopy performed on the sintered samples allowed correlation of the electrical properties of the samples to their microstructures. The sintered nanoprecursors compared with the sintered pure phase powders showed enhanced grain growth associated with higher grain boundary conductivity. The influence of the reactive sintering on the enhanced grain growth and electrical properties in the nanoprecursors is discussed. The high total proton conductivity measured (7.7·10−3 S cm−1 at 450 °C) promotes FSS as an effective powder synthesis method for the preparation of BZY20 electrolyte material for proton conducting fuel cells operating in the intermediate temperature range.